Russian-European relations in the Balkans and Black Sea region : great power identity and the idea of Europe - Samokhvalov, Vsevolod (Palgrave Macmillan, 2020)
Contents: Russian-European relations : an "unexpected" crisis -- Greatness, identity, and method -- Writing Russianness, greatness and Europe in the 1960s -- Writing Russianess [sic], greatness, Europe, and the Balkans in the late Soviet discourse in 1980s -- Russian-European security interaction and the idea of great powerhood between 1991-1999 -- Reinvention of Europe and EU-Russia relations in Putin's era 2000-2010 -- "Black swan" : new greatness, false Europe and the Ukraine crisis (2002-2014) -- Conclusions.